Między stronami mocy. Przyczynek do analizy ustrojowej uniwersów fantastycznych - Stec, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
In popular parlance the Star Wars universe often serves as an example of a binary division between good Rebels and evil Empire. However, a detailed legal analysis of the turbulent political and legal history of the good old Republic and its transformation into the Empire casts doubts on this popular opinion.The Republic seems to be a degenerate system, based on exploitation of the weak, slavery and dominance of the military order the Jedi, exercising power without any democratic control. Surprisingly, the transformation of the Republic into the Empire was formally admissible, and backed up by republican constitutional principles. Moreover, it has been purported here that the political system of the galaxy had very strong feudal relics and allowed both for vendettas and the right to rebel against the goverment. The Rebellion was in fact a counterrevolutionary movement whose main goal was to re-establish the ancient regime and anihilate the last two representatives of the schismatic Jedi sect the Siths, while the Empire was trying to establish a ruthless, but effective system of government. Thus, what we have here is not a battle of Good against Evil but simply a civil war between conservative terrorists and authoritarian reformers. Surprisingly, a short-lived victory of the Rebellion leads to a social and economic crisis, while the restoration of the Empire by the New Order guarantees stability of the economic and political system. Moreover, imperial feuds and vendettas impact only the major players, while the commoners are not directly affected.
Keywords: Gwiezdne Wojny; prawo i literatura; prawo do buntu